The Perception of BPJS Users on The Hospitality Services of a Private Hospital in Denpasar - Sangging, Putu Aryantini; Martini, Ida Ayu Oka (STRADA : Jurnal Ilmiah Kesehatan, 2021)
The government through the Ministry of Health (Kemenkes) issued a new program to provide health social security for the community through Badan Penyelenggara Jaminan Sosial Kesehatan (BPJS) or Social Insurance Administration Organization. This study aims to describe and analyze the perceptions of BPJS users on the hospitality service of a private hospital in Denpasar. The qualitative descriptive research method involved ten respondents consisting of five patients and five families of patients using BPJS Kesehatan. The data analysis technique used interactive analysis. The conclusion from the research on the perception of BPJS users on the hospitality service of a private hospital in Denpasar shows that the BPJS services at RSPR Denpasar are categorized as good; the services include administrative, nursing, medical, and pharmaceutical services. However, there are some complaints from BJPS users regarding the existing facilities at the RSPR.